Determinants of Investment Decisions in the Capital Market Among Generation Z - Sri Murtiasih; Zoya Mayra Fathia (Edunity Kajian Ilmu Sosial dan Pendidikan, 2025)
This study was conducted to analyze the factors influencing investment decisions, namely: the phenomenon of fear of missing out, social media influencers, financial literacy, and risk tolerance on Generation Z’s investment decisions in the capital market, as well as to identify the dominant variable affecting Generation Z’s investment decisions in the capital market. The study used a quantitative method with primary data collected through the distribution of questionnaires to 150 respondents, all of whom were Generation Z individuals who had previously invested in the capital market. The sampling technique employed was non-probability sampling using purposive sampling. Data were analyzed using the PLS-SEM method with the help of SmartPLS software. The results show that fear of missing out, financial literacy, and risk tolerance have a positive and significant influence on Generation Z’s investment decisions, whereas social media influencers do not have a significant effect on Generation Z’s investment decisions in the capital market. Financial literacy is the dominant variable influencing Generation Z’s investment decisions in the capital market.